Islamisasi Ilmu Pengetahuan: Pergulatan Pemikiran Cendekiawan Kontemporer - Mustofa Hilmi (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2020)
The debate of experts regarding the perspective of science in Islam is still ongoing. The paradigm of the islamization of science emerged due to the feeling of the Muslims backwardness from advanced Western civilization. This study aims to elaborate on various views of Muslim scholars on the concept of islamization of science. Employing a literature study using descriptive qualitative research, this study indicates that some religious experts assume that there should be no dichotomy between religious and science in general. Religion must be the foundation of every science because they believe that everything, including science, is sourced from Allah. In essence, there is no separation between religion and every scientific discipline. But the Western thinkers have other views that they focus on the development of science in a positive-empirical aspect. The object of knowledge must be observable. They do not recognize the source and method of development of science in which Muslims use the senses, reason, and intuition. The author argues that somebody must support the idea of the islamization of science to restore knowledge according to its nature. The advancement of modern science must lead a Muslim to increase faith in Allah. Perdebatan para pakar mengenai cara pandang konsep ilmu pengetahuan dalam Islam masih belum berakhir. Paradigma islamisasi ilmu pengetahuan muncul di tengah kondisi tertinggalnya umat Islam dari peradaban Barat yang sudah maju. Tulisan ini bertujuan untuk mengelaborasi berbagai pandangan cendekiawan kontemporer tentang konsep islamisasi ilmu pengetahuan. Kajian ini merupakan studi kepustakaan dengan menggunakan jenis penelitian kualitatif deskriptif. Hasil penelitian menunjukkan bahwa agamawan menganggap tidak boleh ada dikotomi antara ilmu pengetahuan agama dan umum. Agama harus menjadi landasan setiap ilmu pengetahuan yang ada karena mereka meyakini bahwa segala sesuatu yang ada termasuk ilmu pengetahuan adalah bersumber dari Allah Swt., sehingga pada hakikatnya tidak ada sekularisme antara agama dengan setiap cabang disiplin ilmu pengetahuan. Namun para pemikir Barat memiliki tinjauan lain. Mereka hanya menitikberatkan pengembangan ilmu pengetahuan secara positif-empiris. Objek pengetahuan harus dapat diobservasi. Mereka tidak mengakui sumber dan metode pengembangan ilmu pengetahuan muslim yang menggunakan panca indra, akal, dan intuisi. Penulis berpendapat gagasan islamisasi ilmu pengetahuan ini harus didukung sebagai upaya mengembalikan ilmu sesuai fitrahnya. Kemajuan sains modern harus mengantarkan umat manusia pada peningkatan iman kepada Allah Swt.